Introduction: Class in/and the media: On the importance of class in media and communication studies - Jakobsson, Peter; Lindell, Johan; Stiernstedt, Fredrik (Nordicom review, 2021)
Social class is one of the most enduring concepts in the social sciences and is associated with many of the key themes and topics across multiple disciplines. Thus, there are many uses to which the concept of social class in media and communication can be put. The ambition of this special issue is to offer a glimpse into the heterogeneity of its uses in the field. While attuned differently in relation to the various approaches and definitions of class, the eight contributions to this special issue collectively focus on the relationship between media and class. One of the ambitions of this special issue is to report on some of the current Nordic scholarship in this growing field of research and to highlight the particularities of the relationship between class, inequality and media in this region. While the special issue also includes contributions from other regions, the main focus is on social class in the Nordic countries. This introductory article begins with a discussion on the concept of social class and its analytical relevance in the contemporary social landscape. We detail the relationship between media and class as manifested in a growing body of research, followed by a brief presentation of the individual contributions to this special issue. Finally, we identify the road ahead and potential research areas for scholars of media and communication concerned about class and social inequality in the twenty-first century.